Integrating Wiki in Hybrid EFL Writing Class: Exploring Indonesian Students’ Perceptions of Its Benefits and Challenges - Hafni, Astrida; Fithriani, Rahmah (Journal of Community Research and Service, 2021)
This case study put forward a hybrid learning practice in English as a foreign language (EFL) writing classroom through the integration of Wiki.  The purpose of this study was to investigate Indonesian students’ perceptions of the benefits and challenges of Wiki integrated in a hybrid EFL writing class. Seventy-nine EFL students enrolled in Advanced Writing 1 classes at a state university in Medan, Indonesia, were recruited to be the participants. The data for this study were collected using three instruments, namely; observation, online questionnaire for all participants, and interview with 10 voluntary participants. The collected data were later analyzed using content analysis.  The results revealed that overall, the participants found Wiki integration in EFL writing classes advantageous because it allows them to have meaningful interactions with their peers while also improving their writing skills. They, however, also identified some functional difficulties when navigating the platform, highlighting the necessity to adapt their past learning processes in order to adopt new, technology-enhanced learning approaches.